Captopril does not Potentiate Post-Exercise Hypotension: A Randomized Crossover Study - Queiroz, Andréia Cristiane Carrenho; Sousa, Julio Cesar Silva, Jr.; Silva, Natan Daniel, Jr.; Tobaldini, Eleonora; Ortega, Katia Coelho; de Oliveira, Edilamar Menezes; Brum, Patricia Chakur; Montano, Nicola; Mion, Decio, Jr.; Tinucci, Taís; de Moraes Forjaz, Claudia Lucia (International Journal of Sports Medicine, 2017)
To evaluate whether captopril (3×50 mg/day) potentiates post-resistance exercise hypotension (PREH) in hypertensives (HT), 12 HT men received captopril and placebo for 4 weeks each in a double-blinded, randomized-crossover design. On each therapy, subjects underwent 2 sessions: Control (C – rest) and Resistance Exercise (RE – 7 exercises, 3 sets to moderate fatigue, 50% of 1 RM –repetition maximum). Measurements were taken before and after 30–60 min (Post1) and 7 h (Post2), and ambulatory blood pressure (BP) was monitored for 24 h. There were no differences in PREH characteristics and mechanisms between the placebo and captopril periods. At Post1, systolic/diastolic BP decreased significantly and similarly after RE with both therapies (Placebo=−13±2/−9±1 mmHg vs. Captopril=−12±2/−10±1 mmHg, P<0.05). RE reduced cardiac output in some subjects and systemic vascular resistance in others. Heart rate and cardiac sympathetic modulation increased, while stroke volume and baroreflex sensitivity decreased after RE (Placebo: +13±2 bpm, +21±5 nu, −11±5 ml, −4±2 ms/mmHg; Captopril: +13±2 bpm, +35±4 nu, 17±5 ml, −3±1 ms/mmHg, P<0.05). At Post2, all variables returned to pre-intervention values. Ambulatory BP was similar between the sessions. Thus, captopril did not potentiate the magnitude and duration of PREH in HT men, and it did not influence PREH mechanisms.
Keywords: hypertension; angiotensin I-converting enzyme inhibitor; blood pressure; autonomic modulation; strength exercise; placebo-controlled